Outcome analysis of palatoplasty in various types of cleft palate - Venkatesh M Annigeri; Jai K Mahajan; Anu Nagarkar; Satinder P Singh (Wolters Kluwer Medknow Publications, 2012)
Aims: To analyse the factors affecting clinical and functional outcome of Veau-Wardill-Kilner palatoplasty in various types of cleft palate. Materials and Methods: Demographic data were retrieved from case records and a detailed speech, language and hearing and an orthodontic analysis were carried out prospectively. Results: Mean age at operation was 2.7 years; whereas mean age at the time of evaluation was 6 years. Most of the patients (43.3%, 13/30) had a bilateral cleft lip and palate. The postoperative fistula had developed in 31% (4/13) of the patients with bilateral clefts and in 17% (1/6) and 9% (1/11) of the patients with left unilateral and isolated cleft palate respectively (P<0.05). Eight per cent (2/24) of the patients operated before 2 years of age developed a fistula as compared to 66.6% (4/6) of the patients who had undergone a repair after 2 years of age (P<0.01). Severe speech abnormality was seen in 33.4% of the patients having postoperative fistula as compared to 16.6% of non-fistula patients (P<0.05). Derangement of speech was found in 66.6% of the patients who had undergone surgery after the age of 2 years as compared to the patients (13%, 3/24) undergoing correction before 2 years of age (P<0.05). Hearing loss was seen most commonly in patients with bilateral cleft palate as compared to the other varieties (P>0.05). Tympanic membrane (TM) abnormalities were also more common in bilateral cleft patients (P<0.05). Mean maxillary arch length, arch circumference and maxillary inter-canine and inter-molar width were significantly reduced as compared to the control group (P<0.001). Conclusions: Socially acceptable quality of speech can be achieved in more than 85% of the patients. The postoperative fistula is associated with poor speech; bilateral cleft and older age being the risk factors for fistula formation. Many patients require audiological surveillance even when asymptomatic. Maxillary growth is impaired in all the patients despite early surgery.